Family Caregiving as Health Work: A Critical Perspective on the Value of Supporting a Loved One Aging at Home - Holland, Mary Rita (Atlantis, 2025)
This paper uses the example of family caregivers in Atlantic Canada to shed light on the invisible emotional labour—or health work—required to maintain the home as a site of care and manage disrupted meanings of home space and family relationships. It provides an overview of feminist political economics perspective to illustrate the history of women’s exploitation, the extent of their invisible health work, and the impact of private home care and aging-in-place policies on their experiences of home. A critical perspective on gendered, familial care providers and their relationship to the care environment contributes to knowledge of the impact of imposing long-term care policy on domestic relationships and places.